(untitled) (Research, Society and Development, 2021)
In a woman’s life, there are several different phases, among which the most outstanding is the gestational phase. During this period, your body goes through several transformations that require some special care. Among these precautions, supplementation with folic acid and ferrous sulfate stand out, as they are essential nutrients in the formation of the fetal neural tube and for reducing any risk of anemia during pregnancy. But according to the survey, some pregnant women are not fully aware of the benefits that this supplementation guarantees them and the fetus. Given the above, the research aims to assess the perception and practice of using folic acid and ferrous sulfate supplementation among pregnant women. This is a qualitative approach research. Data were collected through a semi-structured questionnaire, applied to pregnant women in Family Health Units, in the city of Redenção-PA, with 25 pregnant women and mothers aged between 20 and 35 years old being interviewed. Based on the results, it was possible to observe and identify that the practice of supplementation intake involves complex issues, such as financial conditions, free availability of medicines in health units, clarity on the importance of use and quality prenatal care. It is concluded that inadequate communication between health professionals and pregnant women who do not have information and clarity and do not seek this information can negatively influence the gestational period.